Patient‐reported outcomes in HCC: A scoping review by the Practice Metrics Committee of the American Association for the Study of Liver Diseases. Issue 1 (22nd January 2022) - Serper, Marina; Parikh, Neehar D.; Thiele, Grace; Ovchinsky, Nadia; Mehta, Shivang; Kuo, Alexander; Ho, Chanda; Kanwal, Fasiha; Volk, Michael; Asrani, Sumeet K.; Ghabril, Marwan S.; Lake, John R.; et al.
Abstract: Background and Aims: HCC is a leading cause of mortality in patients with advanced liver disease and is associated with significant morbidity. Despite multiple available curative and palliative treatments, there is a lack of systematic evaluation of patient‐reported outcomes (PROs) in HCC. Approach and Results: The American Association for the Study of Liver Diseases Practice Metrics Committee conducted a scoping review of PROs in HCC from 1990 to 2021 to (1) synthesize the evidence on PROs in HCC and (2) provide recommendations on incorporating PROs into clinical practice and quality improvement efforts. A total of 63 studies met inclusion criteria investigating factors associated with PROs, the relationship between PROs and survival, and associations between HCC therapy and PROs. Studies recruited heterogeneous populations, and most were cross‐sectional. Poor PROs were associated with worse prognosis after adjusting for clinical factors and with more advanced disease stage, although some studies showed better PROs in patients with HCC compared to those with cirrhosis. Locoregional and systemic therapies were generally associated with a high symptom burden; however, some studies showed lower symptom burden for transarterial radiotherapy and radiation therapy. Qualitative studies identified additional symptoms not routinely assessed with structured questionnaires. Gaps in the literature include lack of integration of PROs into clinical care to guide HCC treatment decisions, unknown impact of HCC on caregivers, and the effect of palliative or supportive care quality of life and health outcomes. Conclusion: Evidence supports assessment of PROs in HCC; however, clinical implementation and the impact of PRO measurement on quality of care and longitudinal outcomes need future investigation.